Pachyphytum rogeliocardenasii (Crassulaceae), a new species from northwestern Querétaro, Mexico - Pérez-Calix, Emmanuel; Torres-Colín, Rafael (Phytotaxa, 2018)
Pachyphytum (Crassulaceae) is a genus of perennial plants with ca. 20 species endemic to central Mexico. Pachyphytum rogeliocardenasii is described here as a new species. It is compared to P. garciae, which is morphologically similar. The new species is endemic to the northwestern region of the state of Querétaro where it was found on limestone walls. It is assigned the category of endangered (EN).